Comparison of Efficacy of Different Treatments for Pulmonary Embolism - 范阳 黄鹤 熊君 杨媚 孔彬 廖佳芬 贺王伟 王志强 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
An optimal therapy for pulmonary embolism（PE） was explored by comparing three different methods in order to alleviate the sufferings of PE patients and reduce the mortality. Eighty patients with PE diagnosed by computed tomography angiography（CTA） were treated with thrombolysis, anticoagulation only, or surgery/intervention. The clinical efficacy of different treatments were compared and analyzed. Twenty-four out of the 26 patients（92%） in anticoagulation only group showed improvement in CTA and clinical presentations, which was significantly higher than that in the thrombolysis group（87%, n=39, P〈0.05）. However, there was no significant difference in the rate of mortality between thrombolysis group and anticoagulation only group. In the surgery/interventional group（n=15）, the success rate was 47%, and the mortality rate was 14%. Both of them were significantly different from those in thrombolysis and anticoagulation only groups（both P〈0.05）. Log-rank analysis of the data of 5-year follow-up revealed that the survival time in surgery/intervention group was significantly shorter than in the other two groups（P0.05）. It was suggested that it is of importance to choose the appropriate therapeutic regimen for PE patients. Mortality may be reduced and prognosis may be improved with anticoagulation only and thrombolysis therapy.